Investigation of InGaN-Based Green Micro-Photonic-Crystal- Light-Emitting-Diodes with Bottom, Nanoporous, Distributed Bragg Reflectors - Kuo-Bin Hong; Wei-Ta Huang; Wen-Cheng Hsu; Chang-Ching Tu; Hao-Chung Kuo (Photonics, 2022)
In this work, an InGaN-based, green micro-photonic crystal-light-emitting-diode (µ-PCLED), which incorporates a nanoporous, GaN-distributed Bragg reflector (DBR) to form a Fabry–Perot (FP) cavity, was fabricated and characterized. Simulations for the µ-PCLED’s optical features were systematically performed and analyzed. Numerical results revealed that the p-GaN photonic crystal (PC) with a filling factor of 0.3 is beneficial for improving the coupling constants of the first- and second-order Bragg diffractions. In addition, based on the product of quantum well (QW) and PC confinement factors, four to six pairs of InGaN QWs should be the preferable design. In order to achieve single-wavelength emission and small full-width at half-maximum (FWHM), the thickness of the n-GaN layer was controlled to be thinner than 920 nm, leading to more than 20 nm wavelength separation between two adjacent FP modes. Experimentally, the fabricated InGaN-based µ-PCLED with a mesa diameter of 30 µm can emit 545 nm green light with FWHM of about 10 nm and negligible blue-shift of about 3 nm in spontaneous emission under the injection current of 1 to 10 mA. Our simulation and experimental results demonstrate that the p-GaN PC design can effectively resolve the wavelength instability issue.